Business model innovation through a rectangular compass: From the perspective of open innovation with mechanism design - JinHyo Joseph Yun; Xiaofei Zhao (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
We aim to develop an innovative way to alter existing business models to conquer the growth limits of exponential paradox by applying the open innovation concept to the design of creative business models. Our research question is as follows: How can we innovate existing business models more easily based on our own thinking experiment at the role-place of ourselves in the open innovation knowledge funnel? We built a rectangular compass concept model and carried out social experiments with it for 3.6 years from November 2014 to May 2019 by developing 17 business model patents to validate the model. The rectangular compass concept model has four aspects: over-shooting of modern business models, expanding the bottom of modern business models, cultivating the forward neighborhood of modern business models, and cultivating the backward neighborhood of modern business model. According to our study, open innovation, which is based on a new combination between technologies (protected technology, protectable technology, and social technology) and market (now market, potential market, and social market), is the engine of sustainable business model innovation dynamics.
Keywords: 650; business model; open innovation; bounded rationality; mechanism design; new combination; rectangle compass